Shifting taxes from labor to consumption: Efficient, but regressive? - Nico Pestel; Eric Sommer (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Shifting taxes from labor income to consumption is regularly suggested as a measure to induce work incentives. We investigate the effect of increases in the Value Added Tax on labor supply and the income distribution in Germany, which is compensated by a revenue-neutral reduction in income-related taxes. Based on a dual data base and a microsimulation model of labor supply behavior, we confirm a general regressive impact of such a tax shift in the short run. When accounting for labor supply adjustments, the adverse distributional impact persists for personal income tax reductions, while the overall effects on inequality and progressivity become substantially lower when payroll taxes are reduced, which is due to increased work incentives, especially for low-income households.
Keywords: H21; H23; C63; D31; 330; income and payroll taxes; consumption taxes; microsimulation; labor supply; inequality; Germany